Tellurium and Nano-Tellurium: Medicine or Poison? - Sári, Daniella; Ferroudj, Aya; Semsey, Dávid; El-Ramady, Hassan; Brevik, Eric C.; Prokisch, József (Nanomaterials (Basel, Switzerland), 2024)
Tellurium (Te) is the heaviest stable chalcogen and is a rare element in Earth’s crust (one to five ppb). It was discovered in gold ore from mines in Kleinschlatten near the present-day city of Zlatna, Romania. Industrial and other applications of Te focus on its inorganic forms. Tellurium can be toxic to animals and humans at low doses. Chronic tellurium poisoning endangers the kidney, liver, and nervous system. However, Te can be effective against bacteria and is able to destroy cancer cells. Tellurium can also be used to develop redox modulators and enzyme inhibitors. Soluble salts that contain Te had a role as therapeutic and antimicrobial agents before the advent of antibiotics. The pharmaceutical use of Te is not widespread due to the narrow margin between beneficial and toxic doses, but there are differences between the measure of toxicity based on the Te form. Nano-tellurium (Te-NPs) has several applications: it can act as an adsorptive agent to remove pollutants, and it can be used in antibacterial coating, photo-catalysis for the degradation of dyes, and conductive electronic materials. Nano-sized Te particles are the most promising and can be produced in both chemical and biological ways. Safety assessments are essential to determine the potential risks and benefits of using Te compounds in various applications. Future challenges and directions in developing nano-materials, nano-alloys, and nano-structures based on Te are still open to debate.